PENGARUH MENULIS PENGALAMAN EMOSIONAL DALAM TERAPI EKSPRESIF TERHADAP EMOSI MARAH PADA REMAJA - Fikri, Harry Theozard (Universitas Ahmad Dahlan, 2012)
AbstractThis study focused on the adolescentâs anger, and efforts to manage the emotion of anger. This research used expressive therapy by writing about emotional experience that aims to help adolescents able to express their anger and as a medium of catharsis. The research design was a single group design with âone group pre-test and post-test experimentalâ method. Participants who attend this research are eight male, with age between 16 to 21 years and had high scores on STAXI Scale. Participants were asked to write down their emotional experiences in a book. The result of the Wilcoxon Signed Ranks Test showed a significant decreasing in participantâs anger after writing session. The results show that writing an emotional experience in expressive therapies able to reduce the emotion of anger in adolescent.Keywords: anger, emotion, writing emotional experience therapy.